Bad souls : madness and responsibility in modern Greece - Davis, Elizabeth Anne, 1974- (Online access with subscription: Duke University Press., 2012)
As part of the agreement for Greece to join the EU, the country had to undertake a massive psychiatric reform, moving patients out of custodial hospitals and returning them to the community to be treated as outpatients. In this subtle ethnography, Elizabeth Davis shows how this played out at the edge of the nation, in the border region of Thrace.